2015
DOI: 10.1080/02640414.2015.1017732
|View full text |Cite
|
Sign up to set email alerts
|

High-volume resistance training reduces postprandial lipaemia in postmenopausal women

Abstract: The aim of this study was to compare the effects of 11 weeks of low-volume resistance training (LVRT) and high-volume resistance training (HVRT) on muscle strength, muscle thickness (MT), and postprandial lipaemia (PPL) in postmenopausal women. Thirty-six healthy and untrained postmenopausal women (age, 58.9 ± 5.8 years; 68.6 ± 10.3 kg; and BMI, 26.9 ± 4.8 kg · m(-2)) participated in resistance training 3× per week for 11 weeks (HVRT = 12; LVRT = 13; and control group = 11). Biochemical variables, both pretrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Many of the studies have failed to show a difference in muscle hypertrophy between the routines (12,17,32,34), but not all (10,31). Regarding this, the effect sizes (from pre-intervention to postintervention) of these studies (when analyzed collectively) (10,12,17,31,32,34) have shown a higher effect to HV-RT ( d = 0.8) than LV-RT ( d = 0.5) (the effect size was calculated by the authors of the current study). Thus, a low effect size (Δ d = 0.3) may be observed between one-set and 3-set routines in muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies have failed to show a difference in muscle hypertrophy between the routines (12,17,32,34), but not all (10,31). Regarding this, the effect sizes (from pre-intervention to postintervention) of these studies (when analyzed collectively) (10,12,17,31,32,34) have shown a higher effect to HV-RT ( d = 0.8) than LV-RT ( d = 0.5) (the effect size was calculated by the authors of the current study). Thus, a low effect size (Δ d = 0.3) may be observed between one-set and 3-set routines in muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any effect of exercise training on PPL should be considered a chronic effect only if it is observed at least two days after the last exercise session. In this sense, findings of studies that investigated the effect of training on PPL by administering a test meal less than two days or on undisclosed time after the last exercise session [118][119][120][121][122] cannot be considered as reflecting chronic exercise effects.…”
Section: Exercise Trainingmentioning
confidence: 99%
“…For determination of the energy expenditure for the control, isocaloric, and caloric deficit protocols subjects used the same equipment, and seated on the cycle ergometer for 5 min before starting the protocols. Total energy expenditure was calculated as the sum of the absolute measured VO 2 (l. minÀ1 ) for each minute during protocols (discarding the initial 5 min), multiplied by 3.5 (to obtain the metabolic equivalents), which were multiplied by 5.0 (kcal.L À1 ) [32]. Post-exercise oxygen consumption was not considered for the determination of the caloric content of the meal.…”
Section: Basal Metabolic Rate (Bmr) and Exercise Energy Expenditure A...mentioning
confidence: 99%